LATIHAN SENAM UNTUK MENURUNKAN BERAT BADAN, LEMAK DAN KOLESTEROL - Tesa Hermadianti Putri; Ika Novita Sari; Hanifah Putri Lestari; Juriska Uria Papua (Lembaga Pengembangan Kinerja Dosen, 2021)
Total cholesterol is one indicator to determine the risk of cardiovascular disease. Excessive body fat and obesity can pose risk factors for diabetes, cardiovascular disease, and dyslipidemia. Hypercholesterolemia or increased total cholesterol levels generally do not cause symptoms, so that preventive checks and routine checks of cholesterol levels are needed as a preventive measure for individuals at high risk. Exercise, as we all know, has a clear effect on reducing levels of fat and cholesterol in the body. our blood. Gymnastics is a type of physical exercise that is used as a means of preventing and losing weight as well as a means of rehabilitation or effective therapy.